Technoeconomic analysis of renewable aviation fuel from microalgae, Pongamia pinnata, and sugarcane. (25th April 2013) - Klein‐Marcuschamer, Daniel; Turner, Christopher; Allen, Mark; Gray, Peter; Dietzgen, Ralf G; Gresshoff, Peter M; Hankamer, Ben; Heimann, Kirsten; Scott, Paul T; Stephens, Evan; Speight, Robert; Nielsen, Lars K
Abstract: Technoeconomic analysis of renewable aviation fuels has not been widely considered, despite the increasing global attention that the field has received. We present three process models for production of aviation‐fuel from microalgae, Pongamia pinnata seeds and sugarcane molasses. The models and assumptions have been deposited on a wiki (http://qsafi.aibn.uq.edu.au) and are open and accessible to the community. Based on currently available long‐term reputable technological data, this analysis indicates that the biorefineries processing the microalgae, Pongamia seeds, and sugarcane feedstocks would be competitive with crude oil at $1343, $374, and $301/bbl, respectively. Sensitivity analyses of the major economic drivers suggest technological and market developments that would bring the corresponding figures down to $385, $255, and $168/bbl. The dynamic nature of the freely accessible models will allow the community to track progress toward economic competitiveness of aviation fuels from these renewable feedstocks. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd